Correlation between hepatic steatosis severity diagnosed by ultrasound and metabolic indexes in elderly patients with MAFLD - Zhitang Liang; Renhao Huang; Lingyun Zhang (Frontiers in Medicine)
ObjectiveTo explore the connection between metabolic parameters and the severity of hepatic steatosis determined through ultrasound in elderly individuals with metabolic dysfunction-associated fatty liver disease (MAFLD).Methods4,663 senior individuals who were 65 years of age or older were included in this research. They were examined physically at the Ninghai Street Community Health Service Center in Yantai City between June 7, 2021, and October 15, 2021. There were two categories of individuals identified: the MAFLD group (n = 2,985) and the non-MAFLD group (n = 1,678). Based on liver ultrasonography results, individuals in the MAFLD group were further separated into three groups: mild (n = 2,104), moderate (n = 766), and severe (n = 115). To identify indicators of risk for the severity of hepatic steatosis, metabolic data was contrasted between the groups employing logistic regression.ResultsIn comparison to the non-MAFLD group, the MAFLD group showed significantly elevated levels of body mass index (BMI), blood pressure, gender, age, lipid profile, alanine transaminase (ALT), and fasting blood glucose (FBG; p < 0.05). Among individuals with MAFLD, there was a positive correlation between BMI, FBG, ALT, and aspartate transaminase (AST) levels and the severity of hepatic steatosis (p < 0.05). Logistic regression analysis indicated that BMI, female gender, FBG, ALT, triglycerides (TG), and serum uric acid (SUA) constituted risk factors for increased severity of hepatic steatosis in MAFLD.ConclusionThe severity of hepatic steatosis in elderly MAFLD patients is significantly correlated with female gender, BMI, ALT, FBG, TG, and SUA.